Renaissance: The Rise Of Art, Culture and Science in Europe - Hajar Mahyana; Umar Affandi; Anis; Indah Setiawan; Nurasiah (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This article examines the Renaissance as a period of revival of art, culture, and science in Europe from the 14th century to the modern era, which emerged after the collapse of the Western Roman Empire in 476 AD and the dominance of the church during the Dark Ages. The Renaissance, derived from the Latin "re" (again) and "naitre" (born), marked the transition to the modern era with a more humanistic and worldly Greco-Roman cultural inspiration, beginning in Italy such as Florence before spreading throughout Europe.